Pembelajaran Budaya Terkini: Meningkatkan Karakter Religius, Toleransi, dan Patriotisme Siswa Melalui Permainan Berbasis Kearifan Lokal - Fihayati, Zuyyina; Rezania, Vanda; Machful Indrakurniawan; Muhammad Ispan; Ayu Salsabila; Khoirun Nisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve character with local culture-based learning in the Merdeka Era learning through games. This study uses a qualitative method, with data collection techniques of observation, interviews, and documentation. This study was conducted in class V at MI Muhammadiyah 2 Kedungbanteng Tanggulangin. The results of the study showed that there was a significant increase in students' religious character, tolerance and patriotism through games based on local wisdom. to see and find out how local game-based learning combined with local knowledge affects the development of students' religious character, tolerance, and patriotism. This study seeks to clarify the efficacy of this new teaching strategy through in-depth analysis. The results should be a guideline for curriculum development, policy making, and educational practices to produce moral and broad-minded successors to the country.